THE EFFECT OF FINANCIAL LITERACY, FINANCIAL PLANNING, AND FINANCIAL CONTROL ON THE FINANCIAL PERFORMANCE OF MSMES WITH THE ADOPTION OF DIGITAL FINANCIAL TECHNOLOGY AS A MODERATING VARIABLE IN LHOKSEUMAWE CITY - Muhammad Multazam; Rico Nur Ilham; Frengki Putra Ramansyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the influence of financial literacy, financial planning, and financial control on the financial performance of micro, small, and medium enterprises in Lhokseumawe City and examine the moderating role of digital financial technology adoption. To demonstrate the reporting format of this article before primary data is available, this document uses 364 synthetic observations and analyzes them through partial least squares structural equation modeling. Simulation results indicate that financial literacy (β = 0.214), financial planning (β = 0.267), financial control (β = 0.318), and digital financial technology adoption (β = 0.228) have a positive effect on financial performance. The interaction of technology with literacy (β = 0.083), planning (β = 0.112), and control (β = 0.146) also shows a reinforcing effect. The simulation model explains 67.3 percent of the variation in financial performance. This figure serves only as a methodological illustration and does not represent empirical findings for MSMEs in Lhokseumawe City.